FEATURES OF USING INTERACTIVE LEARNING TECHNOLOGIES IN PRIMARY SCHOOL (Physical Culture and Sport: Scientific Perspective, 2023)
The article is devoted to the issues of interactive education of children of primary school age. The study adopted the definition of interactive learning as dialogic learning, in which there is interaction between the teacher and the learner on the basis of pedagogical, psychological, computer communication in the dialogue mode. Among the features of the construction of interactive learning, a change in the interaction between the teacher and the student is identified: the activity of the teacher is replaced by the activity of younger students, and the task of the teacher is to create conditions for the manifestation of their initiative; the teacher's function becomes an assistant in activities, one of the sources of information. The main characteristics of "interactive" are defined: 1) a special form of organization of cognitive activity; 2) the educational process is organized in such a way that almost all students are motivated for the learning process; they have the opportunity to understand and reflect on what they know and think; 3) the presence of an atmosphere of benevolence, mutual assistance - a form of cooperation; 4) individual, paired, group forms of work can be organized in lessons; 5) business games, work with documents and various sources of information, creative and research tasks are used. The issue of classification of interactive learning technologies is considered. Among the shortcomings, the following are identified: the quality of students' knowledge depends on their activity; insufficiently developed skill of creative work. When using interactive learning technologies, the age characteristics of students should be taken into account. The specified learning technologies in elementary school lessons are focused on the development of: critical thinking, independent thinking, defending one's opinion, a critical attitude towards oneself, the desire to select the best options for educational solutions, the ability to find joint solutions with classmates. The use of interactive teaching methods during lessons in primary school contributes to increasing the interest of younger students in the studied material, the successful mastering of the educational material by students and improving the quality of education
Keywords: education; primary school; interactive learning technologies